Aliran-Aliran Filsafat Pendidikan: Pendekatan dan Penerapannya dalam Konteks Keilmuan - Nurlaela, Nurlaela; Fadjarani, Siti (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2025)
Abstract. This paper aims to examine various philosophical streams that influence education and how these approaches are applied in the context of academic fields. By employing a library research method, this article analyzes relevant literature such as books, journals, articles, and theses discussing the relationship between philosophy and education. Different educational philosophies offer diverse views on the role of education in shaping individuals and society. Each philosophical approach has its strengths and weaknesses, depending on the cultural and social context. This paper also explores how the application of these philosophical streams in academic contexts can optimize the learning process and achieve more inclusive educational goals that align with the evolving demands of society. A comparison of these approaches reveals that no single approach guarantees academic success for all students, as individual and social factors also affect learning outcomes. These findings aim to provide insights for educators and education practitioners in selecting and adapting the philosophical streams most suitable for contemporary educational needs.